Maroons and Mi’kmaq in Nova Scotia, 1796-1800 - Chopra, Ruma (Acadiensis, 2017)
Forcibly relocated by the Jamaican government, the Maroons of Trelawney Town, Jamaica, reached Halifax in July 1796. Lieutenant-Governor John Wentworth, former loyalist governor of New Hampshire, experimented with integrating and converting these 150 uprooted black families, refugees of war. His self-congratulatory benevolence created and extended the fractured relationships among black and Aboriginal communities in the region. This article helps demonstrate the limits of British paternalism and the far-reaching consequences of distinguishing people of African ancestry from Aboriginal people.